2016
DOI: 10.1104/pp.15.01842
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Protein S-Nitrosylation by Isoprene Emission in Poplar

Abstract: ORCID IDs: 0000-0002-3422-4083 (J.M.-P.); 0000-0001-8410-5624 (J.B.); 0000-0002-9825-867X (J.-P.S.).Researchers have been examining the biological function(s) of isoprene in isoprene-emitting (IE) species for two decades. There is overwhelming evidence that leaf-internal isoprene increases the thermotolerance of plants and protects them against oxidative stress, thus mitigating a wide range of abiotic stresses. However, the mechanisms of abiotic stress mitigation by isoprene are still under debate. Here, we as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 114 publications
(151 reference statements)
4
34
0
Order By: Relevance
“…The PPDB (The Plant Proteome Database) was used to allocate in MapMan BIN categories (Thimm et al, 2004;Usadel et al, 2009). The differences in the proteome of IE and NE genotypes were analysed using Orthogonal Partial Least Square regression (OPLS) statistical methods as previously described in details (Vanzo et al, 2016;Velikova et al, 2014). The results were validated by "full cross-validation" (Eriksson et al, 2006) and in Arabidopsis (Figure 1; Figure S2).…”
Section: Label-free Analysis Of Fine Root Proteomes Using Progenesimentioning
confidence: 99%
“…The PPDB (The Plant Proteome Database) was used to allocate in MapMan BIN categories (Thimm et al, 2004;Usadel et al, 2009). The differences in the proteome of IE and NE genotypes were analysed using Orthogonal Partial Least Square regression (OPLS) statistical methods as previously described in details (Vanzo et al, 2016;Velikova et al, 2014). The results were validated by "full cross-validation" (Eriksson et al, 2006) and in Arabidopsis (Figure 1; Figure S2).…”
Section: Label-free Analysis Of Fine Root Proteomes Using Progenesimentioning
confidence: 99%
“…In that case, the non-emitting poplars were slightly more sensitive to abiotic stress. These genetic tools are being used with microarray technology (Behnke et al 2010;Harvey & Sharkey 2016), proteomics (Vanzo et al 2016), metabolomics (Way et al 2013) and metabolic flux analyses (Ghirardo et al 2014). The suppression of isoprene emission through genetic alteration causes changes in gene expression, especially some transcription factors associated with abiotic stress resistance, changes gene expression related to anthocyanin production and changes nitrosylation state of some proteins.…”
Section: The Discovery Of Specific Inhibitors and Development Of Genementioning
confidence: 99%
“…; Vanzo et al . ), thereby indirectly providing a general antioxidant action (for review, see Vickers et al . ; Loreto & Schnitzler ).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary metabolites (volatile and nonvolatile) are often efficient scavengers of excessive reducing power under stressful conditions (Agati et al 2012;Harrison et al 2013;Esteban et al 2015). It has been suggested that, among volatile isoprenoids, isoprene regulates both reactive oxygen and nitrogen species formation (Behnke et al 2010a(Behnke et al , 2010bVelikova et al 2012;Vanzo et al 2016), thereby indirectly providing a general antioxidant action (for review, see Vickers et al 2009;Loreto & Schnitzler 2010). It is also shown that isoprene stabilizes thylakoid membrane structure and its function is closely associated with structural organization and functioning of plastidial membranes (Velikova et al 2011Pollastri et al 2014).…”
Section: Introductionmentioning
confidence: 99%